The attributions of technologies in art from and their contributions to contemporary education (Research, Society and Development, 2022)
This article aims to investigate how the interaction between art and technology has been occurring in contemporary society. It addresses the existing relationships between Art and Education, Art and Technology and Education and Technology precisely because these three themes are inserted in the educational environment. Whether in the pedagogical aspect or in the personal aspect, artistic knowledge is indispensable for the socio-cultural evolution of people. This research seeks to explain the relationship between Art and technology and its impacts on the teaching process and how they interact in an increasingly digital society. In the final considerations, it is shown how Art and Technology can contribute to the training process of students from transformations that will result positively in Brazilian education and in society as a whole.